Direito ao convívio familiar e os desafios do cárcere: um estudo de caso no sistema penitenciário de Mossoró/RN - Silva, Luine Emmile Lima e (Universidade Federal Rural do Semi-Árido, 2018)
The present work contributes to the debates surrounding the right to family life, especially when the parents are deprived of their liberty and have children of children and / or adolescents. It was briefly described the legal treatment offered to the family by the post-constitutional order and related the right to family life and the right to visit prisoners, considering the changes provoked by Law 12.962/14, through a bibliographical review. Using the jurisprudential research, it was clarified the position of STF and STJ on the subject. Also, by means of data collection and structured interviews, the compatibility of legal provisions and the right to family coexistence were analyzed in the context of the Mossoro/RN’s Federal Penitentiary and the State Agricultural Criminal Complex Mario Negocio. Finally, it was possible to conclude the relevance of family coexistence for both children and adolescents, as well as their parents deprived of their liberty, with violations in the local reality.
Artigo Acadêmico
Keywords: Convivência familiar; Ressocialização; Direito de visitas; Family life; Resocialization; Right of access; CIENCIAS SOCIAIS APLICADAS::DIREITO